SENAM LANSIA UNTUK MEMBANTU MENINGKATKAN KUALITAS HIDUP DAN MENAMBAH STAMINA - Susilawati, Susilawati; Sumarni, Sumarni (Yayasan Nusantara Hasana Berdikari, 2026)
At this age, older adults typically experience a decline in physical fitness, mental health, and cardiovascular function. Furthermore, unhealthy lifestyles have led to an epidemiological shift, shifting the burden of disease from infectious diseases to non-communicable diseases such as hypertension. Various strategies have been attempted to improve the health and nutritional status of older adults. One such strategy is through regular physical activity and exercise appropriate to the elderly's physical condition. This Community Service program aims to improve the quality of life of older adults and increase stamina through gymnastics in the Bajoe Community Health Center (Puskesmas) working area in Bone Regency. The methods used in this Community Service activity include elderly gymnastics to improve quality of life and stamina, counseling, outreach, and coaching on community health programs, as well as training community members to adopt healthy lifestyles. The results of this Community Service activity indicate an improvement in the quality of life of older adults and an understanding of its benefits for their health. The conclusion is that this elderly gymnastics program aims to increase the enthusiasm of residents, especially older adults, in maintaining their health due to the frequent physical and mental health problems that older adults experience.